PERLINDUNGAN TERHADAP DATA PRIBADI DALAM BERSELANCAR DI DUNIA MAYA - Wijaya, Johan; Nursanthy, Aji Titin Roswitha; Thamrin, Muhammad Arganata (The Juris, 2024)
Cyberspace is an electronic medium connected through a computer network, used for online communication. Cyberspace is an integration of various communication technology tools and computer networks that connect communication devices across the globe. Cyberspace has transformed the way people live, work, and interact with one another. Examples of cyberspace include online gaming platforms and social networks. This research addresses the issue of protecting personal data while navigating cyberspace. It is a library research study based on a literature review. In this paper, the author employs a normative juridical approach. Due to its methodology, this type of legal research is referred to as normative legal research. Legal provisions serve as the primary legal materials, particularly Law Number 27 of 2022 on Personal Data Protection (PDP Law). The PDP Law aims to guarantee citizens' rights to personal protection and to raise public awareness of the importance of personal data protection. This study also refers to the Electronic Information and Transactions Law (ITE Law) and its amendments. Article 26, paragraph (1) of Law Number 19/2016 stipulates that the use of personal information through electronic media must be carried out with the consent of the concerned individual. Additionally, the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) is referenced. Article 28G, paragraph (1) of the 1945 UUD NRI states that everyone has the right to the protection of themselves, their family, their honor, their dignity, and their property.